IMPLEMENTASI PROGRAM TOKO TANI INDONESIA CENTER (TTIC) DALAM PENYERAPAN PRODUK TANI DI KOTA PADANG - indah puji lestari (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2020)
Abstrak This study aims to determine the implementation of the work program of Toko Tani Indonesia Center (TTIC) in absorbing agricultural products in the city of Padang. In order to answer these problems, 5 speakers were used. The process of gathering information is done by interview. The analytical tool used is qualitative. In accordance with the results of the interviews that have been conducted, it is known that for the short term the implementation of the Toko Tani Indonesia Center (TTIC) program in the absorption of agricultural products in the city of Padang has proceeded according to the procedure with a fairly good success rate. Nevertheless there are still a number of technical obstacles that affect the implementation of the Padang Tani Indonesia Center (TTIC) work program. Key words : Implementation, Program, Indonesian farm shop center